2017
DOI: 10.2147/copd.s99318
|View full text |Cite
|
Sign up to set email alerts
|

Pri-microRNA-124 rs531564 polymorphism minor allele increases the risk of pulmonary artery hypertension by abnormally enhancing proliferation of pulmonary artery smooth muscle cells

Abstract: MicroRNA-124 (miR-124) has been reported to be downregulated in the cells exposed to hypoxia, which was confirmed in our study. We then used online microRNA target prediction tools to identify GRB2, SMAD5, and JAG1 as the candidate target genes of miR-124, and we next validated GRB2 as a direct gene by using luciferase reporter system. We also established the regulatory relationship between miR-124 and GRB2 by showing the negative linear relationship between GRB2 and miR-124 expression. Furthermore, we investi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 36 publications
0
11
0
Order By: Relevance
“…In our miRNA-disease association analysis, coronary artery disease was one of the disease terms associated with has-miR-124-3p. In human pulmonary artery smooth muscle cells www.nature.com/scientificreports/ in vitro, hsa-miR-124-3p was shown to target GRB2 34 . The ERK2/GRB2/Shc pathway is critical in vascular smooth muscle cell proliferation, and this indicates that differential expression of hsa-miR-124-3p might be involved in the pathogenesis of pulmonary artery hypertension in patients with COPD.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In our miRNA-disease association analysis, coronary artery disease was one of the disease terms associated with has-miR-124-3p. In human pulmonary artery smooth muscle cells www.nature.com/scientificreports/ in vitro, hsa-miR-124-3p was shown to target GRB2 34 . The ERK2/GRB2/Shc pathway is critical in vascular smooth muscle cell proliferation, and this indicates that differential expression of hsa-miR-124-3p might be involved in the pathogenesis of pulmonary artery hypertension in patients with COPD.…”
Section: Discussionmentioning
confidence: 99%
“…Age (year) a 45 49 Height (cm) a 180 178 Weight (kg) a 89 (63-121) 90 Body mass index (kg/m 2 ) a 27 (22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36) 27 (23)(24)(25)(26)(27)(28)(29)(30)(31)(32) Cold (in %) 19 27 Farm childhood (in %) 36 46…”
mentioning
confidence: 99%
“…In addition, previous studies have suggested that hypoxia induces miR-124 downregulation which promotes prostate cancer cell survival, leads to chondrogenesis, and promotes proliferation of pulmonary artery smooth muscle cells. These functions are mediated by the regulation of PIM1 , NFATc1 , and GRB2 , respectively (Gong et al 2017; Gu et al 2016; Li et al 2017). The downregulated miR-124 also exhibits a cardio-protective effect by attenuating endoplasmic reticulum stress (Bao et al 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Hu et al 2010 reported that upregulated hypoxia-responsive miR-210 exhibits a cardio-protective effect by inhibiting Efna3 and Ptp1b , in a mouse model of myocardial infarction. Besides, it is widely reported that miR-124 is a downregulated hypoxia-responsive miRNA involved in the regulation of biological processes in a variety of cells (Gong et al 2017; Gu et al 2016; Li et al 2017). Moreover, a line of evidence has demonstrated that rs531564 (G>C), a functional SNP of the primary miR-124 ( pri-miR-124 ) sequence, is associated with the expression of mature miR-124.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation